2018
DOI: 10.1021/acs.jpclett.8b03750
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Lead Chloride/Bromide Perovskite Quantum Dots with Strong Blue Emission Realized via a Nitrate-Induced Selective Surface Defect Elimination Process

Abstract: Cesium lead halide perovskites emitting blue light in the 460−470 nm range of wavelengths have so far been plagued with rather poor luminescent performance, placing inevitable limitations on the development of perovskite nanocrystal-based blue light-emitting devices. Herein, a selective surface defect elimination process with the help of hydrated nitrates was introduced into the perovskite/toluene solution to strip the undesired surface defects and vacancies and to boost the photoluminescence quantum yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 41 publications
4
94
0
Order By: Relevance
“…[111][112][113] In order to increase their stability, the organic moiety may be partially or totally eliminated. [114][115][116] Caesium(I) is a suitable large cation that can be easily incorporated into lead-based perovskites, both in mixed-cation perovskites 117,118 and in fully inorganic CsPbI 3 perovskites. 119,120 Despite a remarkable initial PCE of 10%, 121 inorganic CsPbI 3 underwent an irreversible transformation toward a non-perovskite phase.…”
Section: High-temperature Processed Front Electrodesmentioning
confidence: 99%
“…[111][112][113] In order to increase their stability, the organic moiety may be partially or totally eliminated. [114][115][116] Caesium(I) is a suitable large cation that can be easily incorporated into lead-based perovskites, both in mixed-cation perovskites 117,118 and in fully inorganic CsPbI 3 perovskites. 119,120 Despite a remarkable initial PCE of 10%, 121 inorganic CsPbI 3 underwent an irreversible transformation toward a non-perovskite phase.…”
Section: High-temperature Processed Front Electrodesmentioning
confidence: 99%
“…Due to the dynamic and labile surface ligands of ionic lead halide perovskite NCs, postpreparative treatment of perovskite NCs by additives containing halides has emerged as a powerful tool to compensate their surface uncoordinated lead ions and thus to improve their PL QY . We have previously demonstrated how the post‐treatment with inorganic nitrate ions can mildly remove surface defects from CsPb(Cl/Br) 3 NCs . Herein, we present a strategy for achieving CsPb(Cl/Br) 3 perovskite NCs with blue emission centered at 451 nm, with high PL QYs of 89% using anhydrous oxalic acid (OxA).…”
Section: Pl Peak Positions Pl Qys Average Pl Lifetimes and Radiatimentioning
confidence: 99%
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%